Management of Information Systems and Services: A Course Module - Seetharama, S. (Journal of Information and Knowledge, 2014)
Discusses the inputs from management science, information technology and economics into the development of information systems and services. Delineates the objectives in providing education in these fields to library and information professionals. Provides a course module for management education.